Educational Technology Professional Development in Higher Education: A Systematic Literature Review of Empirical Research - Lidolf, Sylvie; Pasco, Denis (Frontiers in Education, 2020)
The purpose of this study was to present a systematic literature review of empirical research in the emerging field of faculty members’ educational technology professional development (ETPD). The focus of faculty members’ ETPD is to ensure pedagogically sound technology use in the classroom. Thirty-five articles were identified from a systematic literature investigation, and the results revealed three postures that faculty members may adopt to promote their ETPD: faculty-as-learner, faculty-as-designer, and faculty-as-researcher. These results may help inform stakeholders and policymakers regarding key markers of faculty members’ ETPD based on empirical evidence, to promote a sustainable and scalable educational change.